Direct Detection of Point Mutations in Nonamplified Human Genomic DNA - D’Agata, Roberta; Breveglieri, Giulia; Zanoli, Laura M; Borgatti, Monica; Spoto, Giuseppe; Gambari, Roberto (Analytical chemistry (Washington), 2011)
Ultrasensitive detection protocols not requiring polymerase chain reaction (PCR)-mediated target DNA amplification are expected to significantly improve our possibilities in several research and diagnostic applications for which minute cell quantities are available. For this reason we have tested a nanoparticle-enhanced surface plasmon resonance imaging (SPRI) sensing strategy to detect point mutations in nonamplified genomic DNA. We have used genomic DNAs, not subject to costly, time-consuming, and prone to contamination PCR-based amplification procedures, obtained from both healthy individuals and homozygous or heterozygous patients affected by β-thalassemia, in order to demonstrate the specificity and the sensitivity of the described sensing strategy. The assay we describe is ultrasensitive and convenient. Attomolar concentrations of target genomic DNA are detected, DNAs from healthy individuals and homozygous or heterozygous patients affected by β-thalassemia are discriminated, and only simple manipulations of the genetic samples are required before the analysis. The proposed ultrasensitive detection of DNA point mutations involved in genomic disorders possibly represents an important advantage in several biomedical applications.